2000
DOI: 10.1091/mbc.11.10.3495
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Translocation of Neurofilaments along Microtubules Mediated in Part by Dynein/Dynactin

Abstract: Neuronal cytoskeletal elements such as neurofilaments, F-actin, and microtubules are actively translocated by an as yet unidentified mechanism. This report describes a novel interaction between neurofilaments and microtubule motor proteins that mediates the translocation of neurofilaments along microtubules in vitro. Native neurofilaments purified from spinal cord are transported along microtubules at rates of 100-1000 nm/s to both plus and minus ends. This motion requires ATP and is partially inhibited by van… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
142
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(153 citation statements)
references
References 64 publications
11
142
0
Order By: Relevance
“…Retrograde NF transport also is observed (Yabe et al, 1999;Roy et al, 2000;Wang et al, 2000), which is consistent with the interaction of NFs with a dynein-like motor (for review, see Brady, 2000;Shea and Flanagan, 2001). In this regard, dynein transports NFs along microtubules under cell-free conditions (Shah et al, 2000). The ability of fast axonal transport motors such as kinesin and dynein to translocate NF subunits despite their overall translocation at a rate consistent with slow transport (Nixon, 1992(Nixon, , 1998Hirokawa, 1993;Galbraith and Gallant, 2000;Shea, 2000) is explained by the observation that NFs undergo short bursts of rapid transport that are interrupted by prolonged pauses (Roy et al, 2000;Wang et al, 2000;Ackerley et al, 2003).…”
Section: Introductionsupporting
confidence: 60%
See 3 more Smart Citations
“…Retrograde NF transport also is observed (Yabe et al, 1999;Roy et al, 2000;Wang et al, 2000), which is consistent with the interaction of NFs with a dynein-like motor (for review, see Brady, 2000;Shea and Flanagan, 2001). In this regard, dynein transports NFs along microtubules under cell-free conditions (Shah et al, 2000). The ability of fast axonal transport motors such as kinesin and dynein to translocate NF subunits despite their overall translocation at a rate consistent with slow transport (Nixon, 1992(Nixon, , 1998Hirokawa, 1993;Galbraith and Gallant, 2000;Shea, 2000) is explained by the observation that NFs undergo short bursts of rapid transport that are interrupted by prolonged pauses (Roy et al, 2000;Wang et al, 2000;Ackerley et al, 2003).…”
Section: Introductionsupporting
confidence: 60%
“…Although NFs undergo predominantly anterograde axonal transport (for review, see Shea and Yabe, 2000), many studies in culture and in situ also demonstrate that some NFs undergo retrograde subunit transport (Glass and Griffin, 1991;Watson et al, 1993;Koehnle and Brown, 1999;Yabe et al, 1999Yabe et al, , 2001aRoy et al, 2000;Shah et al, 2000;Wang et al, 2000). Retrograde NF transport may be mediated by the retrograde motor dynein (Shah et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With respect to motility, it has been demonstrated that peripherin and NF containing short filaments (or squiggles) move along MT tracks at rates up to 1-2 m/s in association with the molecular motors, kinesin, and cytoplasmic dynein (Yabe et al, 1999(Yabe et al, , 2000Prahlad et al, 2000;Shah et al, 2000;Wang et al, 2000;Helfand et al, 2002Helfand et al, , 2003. From these observations, it seems that the mechanisms governing the intracellular transport of short NF and peripherin squiggles are not fundamentally different from each other.…”
Section: Discussionmentioning
confidence: 99%